(NfORTEPIANOs (NMETODIKA(B.(Nu^EBNOE POSOBIEs - (N{AHLO sAIDOWAs ((NtA[KENTs (NgOSUDARSTWENNAQ KONSERWATORIQ uZBEKISTANAs, 2024)
(NU^EBNOE POSOBIE PREDNAZNA^EN DLQ BAKALAWRIATA PO NAPRAWLENI@ ISPOLNITELXSKOE ISKUSSTWA (B.s
Keywords: (NmETODIKAs